Autism Spectrum Disorder: a Two-center Evaluation of Pharmacological Intervention and Behavioral Therapies on Core Symptoms - Solek, Purboyo; Gamayani, Uni; Rusmil, Kusnandi; Afriandi, Irvan; Prasetya, Taufan; Rizqiamuti, Anggia Farrah; Nurfitri, Eka; Burhan, Burhan; Sahril, Indra; Gunawan, Kevin (Global Medical & Health Communication (GMHC), 2024)
Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder characterized by chronic deficits in social communication and interaction, with sensory processing abnormalities affecting over 90% of individuals across different sensory areas. This study investigated the combined effects of aripiprazole and behavioral therapy (BT) on core symptoms of ASD in children aged 6–10. Utilizing the considerable neuroplasticity still present at this age, we hypothesized that this combined approach might yield superior outcomes compared to BT alone. The 12-week randomized, double-blind, placebo-controlled trial was conducted from February 2023 to January 2024 at two sites of Child Development Centers in Bandung city, involving 51 participants (22 intervention, 29 placebo). The intervention group received aripiprazole and BT, while the placebo group received saccharum lactis and BT. Both groups underwent BT comprising applied behavioral analysis (ABA) and discrete trial training (DTT). The Childhood Autism Rating Scale (CARS) assessed treatment effects. The independent 2-sample t-tests and Mann-Whitney tests showed no significant differences in overall CARS scores between groups. However, the analysis revealed significant improvements in three subcategories: VII (visual response, p=0.021), IX (taste-smell-touch response, p=0.035), and X (fear or nervousness, p=0.043). These findings suggest that the combined approach may enhance sensory processing and emotional regulation in children with ASD. The study highlights the potential benefits of a multimodal approach to ASD treatment, combining targeted pharmacological intervention with behavioral therapies. However, limitations such as study duration and sample size warrant further research to optimize treatment strategies for individuals across the autism spectrum. DOI: https://doi.org/10.29313/gmhc.v12i3.14460